2005
DOI: 10.3327/jnst.42.1017
|View full text |Cite
|
Sign up to set email alerts
|

Development of Electrochemical Separation Methods in Molten LiF-NaF-KF for the Molten Salt Reactor Fuel Cycle

Abstract: Electrochemical methods for the separation of fission products from fission material in molten fluoride salt media have been studied in the context of their application within the framework of the developed Molten Salt Reactor fuel cycle. The separation possibilities of selected actinides (U, Th) and lanthanides (Nd, Eu, Gd) in molten eutectic LiF-NaF-KF at 530 C were evaluated by means of cyclic voltammetry. The applicability of different electrochemical techniques is discussed with reference to the new resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 4 publications
1
8
0
Order By: Relevance
“…However, it does not mean that the mass transfer is controlled predominantly by diffusion. Shape of this voltammogram is in a reasonable agreement with the previous works [9,43,50]. In all cases, a two-step mechanism was published.…”
Section: Nisupporting
confidence: 91%
See 2 more Smart Citations
“…However, it does not mean that the mass transfer is controlled predominantly by diffusion. Shape of this voltammogram is in a reasonable agreement with the previous works [9,43,50]. In all cases, a two-step mechanism was published.…”
Section: Nisupporting
confidence: 91%
“…Utilization of liquid fuel mix in MSR concepts provides its continual (online) reprocessing. The electrochemical techniques [9] together with molten salt/liquid metal extraction and fluoride volatility method are regarded as usable methods for online processing in terms of the MSR fuel cycle.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…26 These results of UF 4 -FLiNaK melt were consistent with the reported researches. 25,26,[28][29][30] For UO 2 F 2 -FLiNaK melt, the anodic peak H 2 ' at 3.48 V in the curve also belonged to the dissolution of Pt electrode and was more positive than that in the blank FLiNaK melt, which might be induced by the passivation of the Pt electrode surface due to the existence of oxidizing UO 2 2+ in the melt. It was found that when the work electrode was passivated, the oxidation potential of passivated electrode could shift positively and the sight anodic current was generated by dissolved passivated film before the oxidation of electrode, 31 which was also observed in UO 2 F 2 -FLiNaK melt as shown in the inset of Fig.…”
Section: Resultsmentioning
confidence: 94%
“…A first rough assessment of such a technique necessarily goes through preliminary electrochemical studies in fluoride electrolytes of interest. These studies are very few on actinides [6][7][8][9][10]. Furthermore, to our knowledge, no electrochemical data in molten fluorides has ever been published on minor actinides.…”
Section: Electrolytic Separationmentioning
confidence: 99%